HUBUNGAN PENGGUNAAN MEDIA PEMBELAJARAN DENGAN HASIL BELAJAR PKN PADA SISWA KELAS X DAN XI DI SMA MUHAMMADIYAH 1 BANJARMASIN - Triani, Diah (Universitas Lambung Mangkurat (ULM), 2014)
Student learning outcomes in class X and XI SMA Muhammadiyah 1 Banjarmasin is very low , it is known that the learning civics teachers notÂ instructional media when presenting the material , associated with logging students understand the content of the subject matter . This study aimed to determine the relationship of learning instructional media with the results of class X and XI at SMA Muhammadiyah 1 Banjarmasin . This study uses a quantitative approach to sampling technique proportionate random sampling. Samples were obtained at random. The data collection was done by using questionnaires, observation , and documentation . Analysis of the results of research used is descriptive analysis and product moment correlation test .The results of this study indicate that the learning media has a significant relationship with student learning outcomes . Visible on Product Moment Correlation test results is equal to 0.510 which is then adjusted to the interpretation table r value then the value of this 0,510 including interval coefficients between 0.41 to 0.599 which is included in the category of medium -level relationships or pretty .Based on these results, it can be suggested that teachers pay more attention to student needs and using learning media to improve student learning outcomes . Besides, the school is expected to provide infrastructure facilities that support the development of learners.Keyword: instructional media, learning outcomes, student